Have You Asked for It? An Exploratory Study About Maltese Adolescents' Use of Ask.fm. Issue 6 (November 2019) - Farrugia, Lorleen; Lauri, Mary Anne; Borg, Joseph; O'Neill, Brian
This article focuses on adolescents' use of anonymous social networking sites (SNSs). Their perceptions and attitudes toward one such platform, Ask.fm, are discussed using the framework of uses and gratifications theory to explore motivations for using it. Four focus groups and four interviews were carried out with 22 Maltese adolescents (10 female and 12 male) aged 11 to 16 years. Thematic analysis of data collected was undertaken to identify and develop themes relevant to Ask.fm use. Findings indicate that the platform is a space where adolescents interact with others as part of their identity exploration. The role of anonymity was salient throughout. Ask.fm users were aware of the risks related to using the site; yet, the possibilities for fun, peer acceptance, and identity exploration may be driving them to experiment with this risky behavior. The implications arising from these exploratory findings may be applicable to other anonymous SNSs.